STATE OF DEGRADATION IN LOCATED MALLINES IN THE CENTER WEST OF THE COUNTY DE NEUQUÉN (ARGENTINA) - Peña, Oscar Ricardo (2013)
In Patagonia there are wetland ecosystems that have called “mallines” and its vegetation is favorable for livestock use. Management performed over time, mainly due to overstocking has caused in many different states of degradation mallines. The objective in this study is to analyze the status of two mallines located in the Central West of the Province of Neuquén. The results showed in the case of private mallin proper management of livestock which is manifested in supplemental irrigation and stocking acceptable, allowed keeping it in good condition over time and even enhancing areas suitable for livestock. In the second mallin “Laguna Blanca” shows the progressive deterioration of vegetation classes that appear, showing a succession of species with hydrophilic to xerophilic and mesophilic or halophilic and loss of organic soil. This shows effects of disturbance in some cases irreversible.